Environment, Colonization, and the Baltic Crusader States. Terra Sacra I, and Ecologies of Crusading, Colonization, and Religious Conversion in the Medieval Baltic. Terra Sacra II - Maleszka, Anna (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2021)
Environment, Colonization, and the Baltic Crusader States. Terra Sacra I, and Ecologies of Crusading, Colonization, and Religious Conversion in the Medieval Baltic. Terra Sacra II. Edited by Aleksander Pluskowski. Turnhout: Brepols Publishers n.v., 2019. Author’s studies funded by the National Science Centre, Poland’s (NCN) PRELUDIUM grant no. 2016/23/N/HS3/00660.